(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
The aim of this paper was to propose a possible definition of reperformance, comparing it with the general problem of the relationship between presence and archive in the field of performance art. For this, the historical emergence of the reperformance in 2000s was considered through Marina Abramović’s exhibition Seven Easy Pieces, with emphasis on the analysis of the artwork entitled Seedbed, taking into account its similarities and differences with the “original” performance by Vito Acconci. As conclusion, the notion of “archival reduction” was proposed as a central category for the reperformance definition, considering its dialogical and transhistorical potentialities.